A deadly feast - Burdette, Lucy (Burdette, Lucy. Key West food critic mystery., 2020)
"Key West food critic Hayley Snow scents-es something fishy when a customer falls stone-crab cold dead on a seafood tasting tour. Thanksgiving is nearly here, and Key West food critic Hayley Snow has just one more assignment to put to bed for Key Zest magazine before she gets to celebrate with her family and her police officer fiancé, Nathan Bransford. Then, just days later, wedding bells will ring--if death doesn't toll first. The sweet potatoes and stuffing will have to wait when Hayley picks up a distraught phone call from her friend, Analise Smith. On the last stop of a seafood tasting tour run by Analise, one of the customers collapsed--dead. With the police on the verge of shutting down the tour--and ruining Annalise's business--Hayley can hardly refuse her friends entreaties to investigate"--Back cover